E-portfolio and Narrative Organization - Almeborg, Sanne (Proceedings of the International Conference on Networked Learning, 2010)
This poster identifies core issues that learning designers need to consider when they plan to utilize an e-portfolio for learning purposes. These issues include questions as why should one use an e-portfolio? Another important question is of course what an e-portfolio is in the first place? Yet another question to be dealt with goes to how an e-portfolio is used? The poster starts by reviewing specific learning and sociological theories to identify two main reasons for using e-portfolios in today's educational institutions. Firstly, the e-portfolio is a tool for collecting learning products across classes, courses and programs and a tool for reflection with the aim to construct a meaningful whole out of all the smaller pieces of learning and/or learning products. Secondly, society needs the educational institutions to prepare students to construct a meaningful life in a world that's often experienced to be chaotic whether we regard it postmodern or not. The poster introduces theory beyond the traditional portfolio theory, that is theory on technology and media, to help bridging the theoretical gap between traditional paper based portfolios and e-portfolios based on interactive flexible hypermedia. The poster thus researches e-portfolios from one specific perspective: The student is seen as the architect and creator of his own portfolio and a narrator of his own learning and identity since the poster suggests that the structuring and re-structuring of an e-portfolio may be interpreted as creation of a narrative by the student.